Lavender Breeding for Winter Hardiness in a Temperate Climate - Viktoriya Kryuchkova; Anastasia Evtyukhova; Sergey Avdeev; Vitaly Donskih; Olga Shelepova; Olga Ladyzhenskaya; Yuri Gorbunov (Horticulturae)
Lavandula angustifolia is a promising essential oil and ornamental crop whose distribution in the temperate zone and northern regions is limited by its low winter hardiness. Analyzing the causes of low winter hardiness will facilitate the selection of the most winter-hardy hybrids. The study goal is to evaluate the climatic conditions and winter hardiness of narrow-leaved lavender and to determine critical conditions for the successful overwintering of plants in the conditions of Moscow. The studies were conducted in the laboratory of cultivated plants of MBG RAS from 2015 to 2022. The research objects were 72 lavender hybrids. The assessment of hybrids’ winter hardiness was carried out after complete snow melt. Average daily temperature, snow cover height, and precipitation were considered daily. Data statistical processing was carried out using Microsoft Excel and PAST 4.5 software. Optimal lavender overwintering conditions were formed in 2018 and the greatest plant damage was observed in 2017. The research years were grouped by winter hardiness structured into clusters, which allowed us to identify common features in climatic conditions and to identify critical periods of the winter period leading to a decrease in winter hardiness. Temperature fluctuations in winter, frequent temperature transitions over the 0 °C mark, high levels of snow cover and the formation of ice deposits led to severe damage to some lavender hybrids. Severe frosts in the absence of snow cover can lead to the death of lavender plants in the temperate zone. Lavender hybrids were grouped by winter hardiness into two clusters and 11 subclusters. A group of hybrids with consistently high resistance has been selected throughout the years of the study; these hybrids are the most promising for further hybridization.